Sine systemate chaos? A versatile tool for earthworm taxonomy: non-destructive imaging of freshly fixed and museum specimens using micro-computed tomography. - Rosa Fernández (Public Library of Science (PLoS), 2014)
In spite of the high relevance of lumbricid earthworms ('Oligochaeta': Lumbricidae) for soil structure and functioning, the taxonomy of this group of terrestrial invertebrates remains in a quasi-chaotic state. Earthworm taxonomy traditionally relies on the interpretation of external and internal morphological characters, but the acquisition of these data is often hampered by tedious dissections or restricted access to valuable and rare museum specimens. The present state of affairs, in conjunction with the difficulty of establishing primary homologies for multiple morphological features, has led to an almost unrivaled instability in the taxonomy and systematics of certain earthworm groups, including Lumbricidae. As a potential remedy, we apply for the first time a non-destructive imaging technique to lumbricids and explore the future application of this approach to earthworm taxonomy. High-resolution micro-computed tomography (μCT) scanning of freshly fixed and museum specimens was carried out using two cosmopolitan species, Aporrectodea caliginosa and A. trapezoides. By combining two-dimensional and three-dimensional dataset visualization techniques, we demonstrate that the morphological features commonly used in earthworm taxonomy can now be analyzed without the need for dissection, whether freshly fixed or museum specimens collected more than 60 years ago are studied. Our analyses show that μCT in combination with soft tissue staining can be successfully applied to lumbricid earthworms. An extension of the approach to other families is poised to strengthen earthworm taxonomy by providing a versatile tool to resolve the taxonomic chaos currently present in this ecologically important, but taxonomically neglected group of terrestrial invertebrates.